2009
DOI: 10.1590/s0101-81082009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Jovens vivendo com HIV/AIDS: a influência da rede de relações, do coping e do neuroticismo sobre a satisfação de vida

Abstract: ResumoObjetivos: Verifi car o efeito das variáveis rede de relações, neuroticismo e estratégias de coping sobre a variável satisfação de vida em jovens soropositivos. Também buscou-se apresentar um perfi l descritivo da amostra para as variáveis investigadas. Método: Participaram 45 jovens soropositivos, com média de idade de 18,7 anos (desvio padrão = 2,7), procedentes de três centros de atendimento da Grande Porto Alegre. Os instrumentos utilizados foram um questionário de dados sociodemográfi cos, a Escala … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
1
0
2
Order By: Relevance
“…The variable "no occupation" was significantly associated with poor or low perception of QOL and had a high score in the Neuroticism factor. These findings corroborate those found by Gaspar, et al [25] and Ferreira, Oliveira and Paniago A search conducted by Serafini and Bandeira [13] found high levels of Neuroticism in the depression facet. According to Castanha, et al [26] AIDS is anchored in psych affective diseases, depression being considered a key element associated with the disease, due to the high scores in this facet observed in people living with HIV.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The variable "no occupation" was significantly associated with poor or low perception of QOL and had a high score in the Neuroticism factor. These findings corroborate those found by Gaspar, et al [25] and Ferreira, Oliveira and Paniago A search conducted by Serafini and Bandeira [13] found high levels of Neuroticism in the depression facet. According to Castanha, et al [26] AIDS is anchored in psych affective diseases, depression being considered a key element associated with the disease, due to the high scores in this facet observed in people living with HIV.…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted in Brazil with young people living with HIV, findings revealed high levels of Neuroticism, in particular regarding the depression facet, such as the feeling of loneliness, low expectations about the future and lack of goals in life [13]. In this study, the Neuroticism factor was shown to be significantly associated with the emotional instability and depression facets.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…No que diz respeito à associação entre características de personalidade e qualidade de vida, a grande maioria dos estudos encontrados está relacionada a grupos clínicos, tais como deprimidos, soropositivos, pacientes com câncer, etc. (Irigaray & Schneider, 2009;Serafini & Bandeira, 2009). Uma pesquisa desenvolvida com estudantes (Nunes, Hutz, & Giacomoni, 2009) procurou investigar a relação entre bem-estar subjetivo e personalidade no modelo dos CGF.…”
Section: Qualidade De Vidaunclassified
“…Segundo as autoras, isso pode ter ocorrido tanto devido ao fator do suporte social facilitar a busca de uma solução para a situação, quanto aos fatores emocionais envolvidos com o amparo (Damião et al, 2009). Já o segundo, investigou uma amostra de jovens soropositivos e encontrou que o grupo de jovens que relataram situações de estresse relacionadas ao HIV utilizou em maior freqüência estratégias de autocontrole, aceitação de responsabilidade, fuga-esquiva e reavaliação positiva; enquanto que o grupo que relatou outras situações utilizou mais a estratégia confronto (Serafini & Bandeira, 2009).…”
Section: Estratégias De Copingunclassified